Mangrove structure and its influence on the carbon storage in La Encrucijada Reserve, Chiapas, Mexico - Velázquez-Pérez, Carolina; Tovilla-Hernández, Cristian; Romero-Berny, Emilio I.; De Jesús-Navarrete, Alberto (Instituto de Ecología, A.C., 2019)
Mangroves have been considered as an important carbon storage, and in general, exceeding the carbon content of terrestrial forests. Even when mangrove aerial carbon sequestration has been studied in several regions of Mexico, the information at the Pacific coast is lacking. The aim of this work was to characterize the structure of riverine mangroves in order to determine height, coverage, DBH and to estimate the complexity and importance value indexes, as well to relate it with the carbon storage, in 32 circular sampling units (400 m2) at La Encrucijada Reserve, Chiapas. The carbon content was quantified according allometric equations for Neotropical mangrove species, with high structural development and we used a biomass to carbon conversion factor of 0.48. The influence of the interstitial sediment parameters (pH, salinity, temperature) on the stored carbon was determined using an analysis of variance and covariance. Mangrove density was 2103 ind ha-1, the tree mean height was 12 m; basal area, 18.7 m2 ha-1; coverage, 9.9 m2 and DAP, 8.4 cm. A complexity index of 40.1 was recorded; the order of importance of the species was Rhizophora mangle / Avicennia germinans / Laguncularia racemosa. The carbon store was 87.0 Mg ha-1. Structural parameters showed a high correlation (R = 1.00, 0.94 and 0.84) with the mangrove biomass. In function of this structure, this ecosystem was classified as a successional stage of intermediate community with a high structural complexity.